Non-Invasive Topical Drug-Delivery System Using Hyaluronate Nanogels Crosslinked via Click Chemistry - Choi, Hyunsik (Materials (Basel), 2021)
Hyaluronate (HA) has been widely investigated for noninvasive topical drug delivery of chemical drugs and biopharmaceuticals. However, previous noninvasive delivery systems have been facilitated mostly by chemical conjugation of drugs with HA, which can cause reduced therapeutic efficacy and safety issues in chemically modified drugs. Here, HA nanogels were synthesized by crosslinking via “click” chemistry for noninvasive topical delivery of a model drug without chemical modification. The model-drug-encapsulating HA nanogels could be uptaken to the skin melanoma cells in vitro by HA-mediated endocytosis. In addition, histological analysis showed that HA nanogels could be topically delivered to the deep skin and tongue tissues through the noninvasive delivery routes. Taken together, HA nanogels could be effectively used for the noninvasive topical delivery of various therapeutic drugs.